High-dose aciclovir in CMV infection prophylaxis after allogeneic HSCT: a single-center long-term experience - Kabut, Tomáš; Weinbergerová, Barbora; Folber, František; Lengerová, Martina; Mayer, Jiří (Bone marrow transplantation, 2023)
There is only limited data on cytomegalovirus (CMV) prophylaxis with high-dose (HD) aciclovir after allogeneic hematopoietic stem cell transplantation (allo-HSCT). We performed a retrospective analysis on a total of 179 patients who underwent their allo-HSCT with HD-aciclovir prophylaxis at our center. A clinically significant CMV infection (cs-CMVi) was observed in 56 (31%) cases with a median time of 49 (range 25-147) days after HSCT. A significantly higher CMV infection rate was observed in seropositive recipients with a seronegative donor (74%) compared to seropositive recipients with a seropositive donor, and seronegative recipients with seropositive and seronegative donors (24%, 18%, 7% respectively; p < 0.001). The CMV serostatus was the only significant risk factor for CMV infection in our analysis. CMV disease developed in three patients with CMV-related death in two cases. During HD-aciclovir prophylaxis, we did not observe any medical condition attributable to HD-aciclovir's adverse effects. Compared to published results, we observed a low incidence of cs-CMVi with HD-aciclovir prophylaxis in several patient subgroups, especially in seropositive recipients with a seropositive donor. With respect to the determined threshold, HD-aciclovir prophylaxis seems to have good efficacy in an intermediate cs-CMVi risk patients, but prospective randomized trials would be needed for definite conclusions.
Keywords: Hematopoietic Stem Cell Transplantation; Acyclovir; antivirové látky; transplantace hematopoetických kmenových buněk; retrospektivní studie; prospektivní studie; Humans; Cytomegalovirus; acyklovir; Prospective Studies; Cytomegalovirus Infections; Antiviral Agents; Retrospective Studies; lidé; cytomegalovirové infekce